Randomized Comparison of Isoflurane versus Sevoflurane and Desflurane for Maintenance of Ambulatory Anesthesia - Kurhekar, Pranjali (Anesth Essays Res, 2017)
BACKGROUND: Ambulatory surgeries demand safe anesthesia with faster recovery which makes it expensive due to the cost of inhalational anesthetic agents such as sevoflurane and desflurane. Isoflurane is inexpensive agent but can cause delayed recovery. The aim of this study was to evaluate cost-benefit ratio of all three agent with respect to recovery and safety profile MATERIALS AND METHODS: Patients posted for elective ambulatory surgeries were divided into three groups. Suitable size laryngeal mask airway was inserted following induction with propofol and vecuronium. Anesthesia was maintained on low-flow anesthesia with inhalational agent as isoflurane for Group I, sevoflurane for Group II and Group III received desflurane. Patients were monitored for recovery as per modified Aldrete score and as per postanesthesia discharge scoring system for discharge from hospital. Cost analysis was done by Dion's formula. Statistical analysis was done with analysis of variance for recovery profile, Chi-square test for safety profile and Kruskal Wallis test for cost comparison between groups. RESULTS: Patient characteristics and duration of anesthesia were similar in all three groups. Time to eye-opening was significantly less with desflurane than sevoflurane and isoflurane (P = 0.001). Time to home readiness was similar in all three groups (P = 0.451). The incidence of airway irritation, pain, and nausea/vomiting was similar in all three groups. Cost of Group I was statistically lower than other two groups (P = 0.00). CONCLUSION: Home readiness and safety profile were comparable between agents; the cost involved was the least with isoflurane.